Chemical Synthesis of Monomeric, Dimeric and Tetrameric Forms of the Ectodomain of Influenza Matrix 2 Protein. Issue 5 (21st January 2016) - Zeng, Weiguang; Horrocks, Kylie J.; Tan, Amabel C. L.; Jackson, David C.
Abstract: The highly conserved ectodomain of M2 protein (M2e) of influenza virus A is one of the most studied vaccine targets for induction of cross‐strain protection. It has been reported that the native form of M2 is a homo‐tetramer linked by disulfide bonds and that antibodies reactive to this form correlate with M2‐mediated protection. Although vaccine constructs mimicking the quaternary structure of M2 have been described, the chemical syntheses of disulfide‐linked dimeric and tetrameric forms of M2e have not yet been reported. By exploiting orthogonal chemistry during the syntheses, we successfully assembled dimeric and tetrameric forms of M2e but found that the antibodies that they elicited had protection properties similar to those of the monomeric form. There was, therefore no advantage mimicking the native conformation to improve vaccine efficacy. Nevertheless, the synthetic strategies have the potential for use in preparation of other dimeric or tetrameric constructs. Abstract : A facile chemical synthesis of the disulfide bond linked tetrameric form of the ectodomain of influenza matrix 2 protein has been established. Acidic conditions were used throughout to minimize randomized thiol‐exchange reactions. The synthetic strategies can be adapted for the preparation of other dimeric or tetrameric constructs.